Konsep Komunikasi Dalam Al-Quran: Prespektif Islam Dalam Meningkatkan Kualitas Komunikasi Individu - Imroatul Mufidah; Desti Nurlita Sari; Ismail Mubarok (Jurnal Multidisiplin Indonesia, 2023)
Communication is a process of conveying messages and information from someone to another someone so that the message in question can be easily understood. This concept has been around since the time of Prophet Adam AS and involves human relationships. According to the Quran, a person is responsible for individuals when it comes to communication. Islam has 6 types of language styles, including Qaulan Sadidan (true and firm words), Qaulan Baligha (words that leave an impression on the soul), Qaulan Ma'rufa (good words), Qaulan Karima (noble words), Qaulan Layina (gentle words), and Qaulan Maysura (proper words). Responsibility is a fundamental trait that humans, especially Muslims, must possess. As Rasulullah SAW said in HR. Bukhari, not being responsible has serious consequences. However, responsibility in Islam also has its advantages and disadvantages, which are influenced by differences in individuals and groups.